2022
DOI: 10.29271/jcpsp.2022.07.869
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines the Etiology of Idiopathic Granulomatous Mastitis

Abstract: Objective: To investigate the roles of cytokines in the etiopathogenesis of idiopathic granulomatous mastitis (IGM). Design: Case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…GLM is an autoimmune disease and cytokines can be used to assess the degree of immune dysregulation in patients, which may play an important role in the pathogenesis of GLM. [29][30][31][32][33] Koksal et al investigated the expression levels of IL-4, IL-8, IL-10 and IL-17 in patients with GLM and showed that the levels of IL-8, IL-10 and IL-17 were significantly increased and the levels of IL-4 were decreased in patients with GLM. 33 IL-4 and IL-10 can be used to assess T helper cell type 2 (Th2) cell function, IL-8 levels can be used to assess neutrophil chemotaxis and IL-17 can be used to assess inflammation and T helper cell type 17 (Th17) cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLM is an autoimmune disease and cytokines can be used to assess the degree of immune dysregulation in patients, which may play an important role in the pathogenesis of GLM. [29][30][31][32][33] Koksal et al investigated the expression levels of IL-4, IL-8, IL-10 and IL-17 in patients with GLM and showed that the levels of IL-8, IL-10 and IL-17 were significantly increased and the levels of IL-4 were decreased in patients with GLM. 33 IL-4 and IL-10 can be used to assess T helper cell type 2 (Th2) cell function, IL-8 levels can be used to assess neutrophil chemotaxis and IL-17 can be used to assess inflammation and T helper cell type 17 (Th17) cell function.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Koksal et al investigated the expression levels of IL-4, IL-8, IL-10 and IL-17 in patients with GLM and showed that the levels of IL-8, IL-10 and IL-17 were significantly increased and the levels of IL-4 were decreased in patients with GLM. 33 IL-4 and IL-10 can be used to assess T helper cell type 2 (Th2) cell function, IL-8 levels can be used to assess neutrophil chemotaxis and IL-17 can be used to assess inflammation and T helper cell type 17 (Th17) cell function. Coskun et al further analysed the changes in cytokine profiles in patients with active and remission GLM, and their results showed that patients with active GLM may have elevated IL-8 and IL-17 and reduced IL-10, but none of these results were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted over the last 10 years have emphasized that other factors such as genetic factors, smoking, and alpha-1 antitrypsin deficiency may have a role in the pathogenesis of the disease. It remains unclear whether GLM is caused by a single factor or a combination of factors (5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Autoimmunity is considered the strongest theory in explaining the cause.…”
Section: Etiologymentioning
confidence: 99%
“…Autoimmunity is considered the strongest theory in explaining the cause. A "secretion hypothesis" stipulates those patients' secretions such as retained milk may stimulate both humoral and cell-mediated immunity (10,11). We should not forget that if many factors are held responsible for the etiology of a disease or if many hypotheses are put forward, we probably know very little regarding the etiology of that disease.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation